Synthesis and Structural Characterization of Three Homotrinuclear Metal Complexes Stabilized by tetradentate N-isopentylidine hydrazinedithiocarbamate Schiff base Ligand (Thamar University Journal of Natural & Applied Sciences, 2023)
The new tetradentate Schiff base ligand (L), which was used as stabilizers for homotrinuclear metal complexes were prepared from condensation of 3-pentanone and ammonium hydrazinedithio-carbamate have been used into in situ reactions with metal chlorides in molar ratio of 3 : 2 (M : L) in ethanol, leads to the Schiff base homotrinuclear metal complexes of the general formula [M3(L)2Cl2(H2O)2] where L = N-isopentylidine hydrazinedithio-carbamate and M= Co (II), Ni(II) and Cu(II), which have been characterized by elemental analysis, molar conductivity and magnetic susceptibility measurements, FT-IR and UV-Vis spectroscopy as well as MM2 calculation by using CsChem3D Ultra program package. The spectroscopic evidences and magnetic data exhibits presence of mixed properties for both the square planar configuration around the center metal ion and the tetrahedral configuration around the two terminal metal ions within the homotrinuclear units.